Design of a dual-polarised wideband source antenna onboard an UAV for radio astronomy element characterisation - Pienaar, H.; Davidson, David (2017)
© 2017 IEEE. A new calibration method for aperture array radio telescopes, using a multi-copter as an artificial source in the near-field, is being investigated. A source with good polarisation performance extending the full instrument bandwidth is necessary to decrease measurement time and ensure accuracy. The primary focus of the paper is the design of a dual polarised, differentially fed, discretely loaded dipole that can be implemented on the multi-copter platform. The compact nature of the multi-copter means that cut-outs in the antenna ground plane are necessary to house other sensors critical for accurate positioning. The antenna was designed using a Wu-King loading profile. A full Finite Difference Time Domain (FDTD) model of the vehicle with the antenna was simulated to investigate the performance of the elements on the compound structure. Some added ripple was introduced into the far-field pattern due to the finite ground plane and complex structure. The depolarising effect of the sensor cutouts was deemed small enough to allow these apertures in the final design.